Effects of Eurycoma longifolia standardized extract on Estradiol valerate-induced teratogenicity in female rats - Ahmad, Nur Amalina; Abdul Rahman, Suzanah; Chan, Kit-Lam; Abdul Samat, Nadia Hanis; Zahri, Syazana; Abdullah, 'Afif Raihan (2017)
Estradiol valerate, a synthetic and steroidal estradiol is used as prescription for the treatment of certain female reproductive disorders as well as contraceptive drugs. Consumption of estradiol valerate during early pregnancy may produce abortional effects especially in cases of unknown pregnancy. Teratogenic effects have also been detected at toxic levels of the agent. This study therefore aims to investigate the possible effects of standardized extract of Eurycoma longifolia, TAF 273, on foetus development in female rats exposed to estradiol valerate. Pregnant female rats on day 12 of gestation (GD12) were administered with a single subcutaneous injection of estradiol valerate (0.15 mg/kg) and were randomly divided into 3 groups of 5 dams each which then received treatment of TAF 273 at doses of 25, 50 and 100 mg/kg body weight orally from day 12 gestation (GD12) until day 19 gestation (GD19). Pregnancy was terminated on day 21 of gestation (GD21) and uterus of each dam was carefully excised and the foetuses were examined for morphological observations. Results showed that exposure to estradiol valerate decreased the number of live foetuses with high number of pre-implantation loss and early resorption. Foetuses in the group treated with 100 mg/kg TAF 273 extract showed high number of live foetuses but with decreased body weight and crown-rump length as the number of embryo in the uterus also affect the availability of space for embryonic development and blood supply which relates to nutrition received by the foetuses. Observations of abnormalities in the form of kyphosis, scoliosis and kinky tail in EV group were more pronounced than in control and treatments group. The present study suggests that Eurycoma longifolia may have potential in ameliorating the teratogenic effects of estradiol valerate by reducing external abnormalities in the rat foetuses. Eurycoma longifolia may have prospective use in the treatment of female-linked disorders and complications.